Management of Dystocia Due to Posterior Presentation andUmbilical Torsion in a Jenny - Kumar, Sajjan; Singh, Jitender; Dedar, Ramesh Kumar; Thirumala Talluri, (The Indian Journal of Animal Reproduction, 2024)
The present case report puts on record successful management of dystocia in a jenny suffering from posterior presentation of fetus and torsion of the umbilical cord. A five-year-old pregnant jenny in its last trimester with the history of vaginal discharges followed by mild straining without any progress was reported at the farm. The vaginal examination revealed a fully dilated cervix with the presence of a fetus with breech presentation. The fetus was relieved successfully by repulsion of the fetus, extension of flexed hind legs and final traction of the fetus without any administration of anesthesia.
Keywords: Jenny; Dystocia; Umbilical cord torsion; Breech presentation